EVALUASI SIFAT FISIK DAN UJI IRITASI SEDIAAN SALEP MINYAK ATSIRI BUNGA CENGKEH DALAM BASIS LARUT AIR - Diah Pratimasari; Nining Sugihartini; Tedjo Yuwono (Universitas Islam Indonesia, 2015)
Essential oil of clove (Syzygium aromaticum) (MABC) with eugenol as its main active ingredient, has been studied as anti-inflammatory agent. Its important to develop formulation in an advanced research. This study has been conducted to develop a topical dosage form (an ointment using a water-soluble base). The physical properties of water-soluble ointment preparation of MABC and the irritation properties at various concentrations of MABC have been evaluated. Ointment preparation MABC water-soluble base created using the mixing of the PEG 400 and PEG 4000 by a fusion method. Ointment made with a various concentration of MABC (5%, 10% and 15%). Ointment with each concentration were evaluated based on its physical properties such as pH, dispersiveness and adhesion. Ointment also tested its irritative properties on the skin, using test animals guinea pigs by Draize test method. Data from those experiments analyzed by ANOVA with T-test level of 95%. The results showed that the physical properties of water-soluble ointment base with MABC concentration of 5%, 10% and 15% reach the requirements of the pH and adhesion parameter, but not for its dispersiveness. Statistical analysis of each trial did not show any significant in difference. The experimental results against irritation test showed that the water-soluble ointment base concentration of 5%, 10% and 15% did not cause irritation to the skin of guinea pigs.